Soil physico-chemical characterization in the different soil layers of National Maize Research Program, Rampur, Chitwan, Nepal - Khadka, Dinesh; Lamichhane, Sushil; Timilsina, Amit P; Baral, Bandhu R; Sah, Kamal; Joshi, Bishnu D; Joshi, Sushila; Adhikari, Parbati (Journal of Maize Research and Development, 2018)
Soil pit digging and their precise study is a decision making tool to assess history and future of soil management of a particular area. Thus, the present study was carried out to differentiate soil physico-chemical properties in the different layers of excavated pit of the National Maize Research Program, Rampur, Chitwan, Nepal. Eight pits were dug randomly from three blocks at a depth of 0 to 100 cm. The soil parameters were determined in-situ, and in laboratory for texture, pH, OM, N, P (as P2O5), K (as K2O), Ca, Mg, S, B, Fe, Zn, Cu and Mn of collected soils samples of different layers following standard analytical methods at Soil Science Division, Khumaltar. The result revealed that soil structure was sub-angular in majority of the layers, whereas bottom layer was single grained. The value and chrome of colour was increasing in order from surface to bottom in the majority pits. Similarly, the texture was sandy loam in majority layers of the pits. Moreover, four types of consistence (loose to firm) were observed. Furthermore, mottles and gravels were absent in the majority layers. Likewise, soil was very to moderately acidic in observed layers of majority pits, except bottom layer of agronomy block was slightly acidic. Regarding fertility parameters (OM, macro and micronutrients), some were increasing and vice-versa, while others were intermittent also. Therefore, a single layer is not dominant for particular soil physico-chemical parameters in the farm. In overall, surface layer is more fertile than rest of the layers in all the pits.